Understanding Parenting Intentions Among Childfree Gay Men: A Comparison With Lesbian Women and Heterosexual Men and Women - van Houten, Joke T.; Tornello, Samantha L.; Hoffenaar, Peter J.; Bos, Henny M. W. (Frontiers in Psychology, 2020)
Introduction. There is a growing interest in the parenting intentions of gay men. Prior research has found that gay men are less likely to become parents compared to their heterosexual and lesbian peers, but we know very little about why this discrepancy exists. Our first aim was to investigate whether the strength of parenting intentions is similar or different among childfree gay men compared to lesbian women, and heterosexual men and women. Our second aim was to explore the extent to which the Theory of Planned Behavior (TPB) model (attitude, subjective norms, and self-efficacy) is universal in predicting the strength of parenting intentions across gender and/or sexual orientation. Method. The study was based on a United States cross-sectional, internet-based survey of childfree people who want to become parents in the future. The sample consisted of 58 gay men, 66 lesbian women, 164 heterosexual people (128 women and 36 men). Results. A Bayesian ANCOVA showed no support for a gender difference in the strength of parenting intentions. Moderate evidence was provided for gay men and lesbian women reporting a similar strength of parenting intentions compared to their heterosexual peers. Bayesian linear regression analyses showed that perceived positive and negative life changes were stronger predictors of the strength of parenting intentions for men than for women. Perceived positive life changes predicted the strength of parenting intentions similarly across sexual orientations. For gay men and lesbian women, perceived parental acceptance of future parenthood was a weaker predictor of the strength of parenting intentions compared to heterosexual people. Conclusion. Those who perceived parenthood as bringing positive life changes, especially for men, expressed stronger parenting intentions.